Linking Veterinary Science Faculty Research and Activities to the UNESCO Sustainable Development Goals: The Role of the Library - Nel, Marguerite Alice; Breytenbach, Amelia (My University, 2023)
There are widespread opportunities for universities to contribute to the implementation of SDGs. Consequently, sustainability is viewed as an essential aspect of a university's reputation, and research applications and grants are increasingly subjected to alignment with SDG targets of research funders. Nevertheless, while there are extensive initiatives and SDG-focused research undertaken by universities, there is still a significant gap in documenting and reporting the evidence and assessing the conformity between activities of teaching, research, community engagement, and campus operations. With academic libraries mandated to align with the core business of the higher education system, it is sensible to explore opportunities to support the strategies of their parent institutions. Libraries are thus responsible for considering ways to support SDG-related initiatives of their faculties. Essentially, librarians are perfectly positioned to apply their information management skills, information organising tools, and information communication infrastructure knowledge to facilitate SDG discovery, retrieval, and promotion. The Jotello F. Soga Library, at the University of Pretoria, serves the Veterinary Science community of South Africa. This paper will report on the initiatives undertaken by librarians at this specialised library to organise, communicate, and promote the SDGs related to veterinary science, especially through utilising the library's open-access platforms.
Keywords: Sustainable Development Goals; Veterinary Science; Libraries